PENERAPAN LEVELS OF INQUIRY UNTUK MENINGKATKAN DOMAIN KOMPETENSI DAN PENGETAHUAN SAINS SISWA SMP PADA TEMA PENCEMARAN LINGKUNGAN - Rohmi, Puspo (2015)
Tujuandaripenelitianiniadalahuntukmengetahuipeningkatan domain kompetensidanpengetahuansainssiswasetelahditerapkannyalevels of inquiry padapembelajaran IPA terpadutemapencemaranlingkungan. Penelitianinimenggunakanmetodepenelitianpre-experimentaldengandesainone-sample pretest posttest design. Data dikumpulkanmelalui instrument tesliterasisainsberbentukpilihanganda, lembarobservasi, LKS, danangket yang diberikansetelahpelaksanaanpembelajaran. Hasilanalisis data menunjukkanbahwaterdapatperbedaan yang signifikanantaraskorpretesdanskorpostessetelahditerapkannyalevels of inquiry. Perbedaan yang signifikantersebutterjadipadasetiap domain padaaspekkompetensidanpengetahuan yang diteliti. Selainitu, hasilperhitunganCohens'dadalah 1.82, dapatdiinterpretasikanbahwapenerapanlevels of inquirymempunyaipengaruh yang besarterhadappeningkatanskor domain kompetensidanpengetahuansainssiswa. Hasilpenelitianmenunjukkanbahwapenerapanlevels of inquiry dalampembelajaran IPA terpadudapatmeningkatkan domain kompetensidanpengetahuansainssiswa. Sebagaikesimpulanyaitupenerapanlevels of inquiry dapatmembantusiswauntukmelatihketrampilaninkuiriuntukmeningkatkanliterasisains yang menuntutpenerapandarikompetensidanpengetahuan yang merekamiliki. Penelitianinijugamenemukanbahwasiswamempunyairesponpositifterhadappenggunaaninkuiri yang dilakukansecarasistematisdalampembelajaran IPA. Kata kunci : levels of inquiry, literasisains, domain kompetensi, domain pengetahuan, IPA terpadu, pencemaranlingkungan. The aim of this study was to determine the enhancement students' competencies and knowledge domain after implementation levels of inquiry on integrated science instruction on the theme of environmental pollution. This study use pre-experimental research method with one sample pretest posttest design. Data collecting through scientific literacy instrument organized as multiple choice test, observation sheet, worksheet, and questionnaire after undertaking the learning process. Analysis of the data showed that there was a statistically significance different between the pretest scores and the posttest scores after implementing levels of inquiry. Significance is shown both domains of competencies and knowledge aspects studied. Furthermore, the results of the Cohens'd calculation was 1.82, it can be interpreted that implementation of levels of inquiry has large effect on enhancement competencies and knowledge domains scores. Results indicated that implementation of levels of inquiry in integrated science lesson can enhanced students' competencies and knowledge aspects of scientific literacy.It was concluded that implementing the levels of inquiry can help students to practice inquiry skills to enhance their scientific literacy which requires the application of competencies and knowledge they have. In addition it was also found that students' have positive response about using inquiry systematically in science instruction. Keywords :levels of inquiry, scientific literacy, competencies domain, knowledge domain, integrated science, environmental pollution.